Carbon Nanotubes: A Targeted Drug Delivery against Cancer Cell - Kumar, Prashant; Pandey, Surya N.; Ahmad, Farman; Verma, Anurag; Sharma, Himanshu; Ashique, Sumel; Bhattacharyya, Subhra Prakash; Bhattacharyya, Indrani; Kumar, Shubneesh; Mishra, Neeraj; Garg, Ashish (Current Nanoscience, 2024)
Drug delivery in human subjects has been the most difficult task since the ancient time of the medical sector. An ideal drug delivery system is, one that minimizes the adverse effects and maximizes the desired effects of the drug candidate. Various drug delivery systems have been developed that may have some kind of advantages and disadvantages, among them targeted drug delivery system is more preferable and convenient which may employ various nanoparticles or other materials for the drug delivery at the specified site of action. In this, the authors elaborately and comprehensively explained the role of recent carbon nanotubes (CNTs) in targeted drug delivery systems (specifically for targeting cancerous cells). The authors also described the methods of preparation of CNTs, characterization techniques for CNTs, cellular penetration of, CNTs, and the associated toxicities with CNTs. Carbon nanotubes are preferable to other nanoparticles because they are more electrically, mechanically, and organically stable than others, they can carry more amount of drug in comparison to other nanoparticles and their functionalization property makes them more attractive as a carrier molecule for targeting any root cause of the disease.
Keywords: SWNTs